Solar drying simulation of different products: Lebanese case. (November 2020) - Brouche, Marwan; Lahoud, Chawki; Lahoud, Mirna F.; Lahoud, Christy
Abstract: The world is acting towards the reduction of use of fossil fuels. Therefore, a big number of innovations are utilized that adopt sources of renewable energy such as wind, solar, tidal etc. Solar radiation is used for different applications, one of them is drying different products from thousands of years. Thus, solar energy was the only used energy until the discovery of fossil fuel sources, especially utilized for solar dryers. These dryers are not very commercialized, and their designs are based on empirical and semi-empirical systems. Therefore, theoretical studies will be of high importance in this field. The majority designs of solar dryer available in the market, are used mainly for drying of various crops either for family use or for small-scale industrial production. In this article a simulation of the Lebanese ambient temperature and the relative humidity will be conducted then compared to the meteorological experimental data. After that, a modeling of a direct solar dryer system is developed based on the heat transfers phenomena inside and outside the dryer. This model is simulated using five different products that helps us to determine the instant temperatures of the product, of the internal air of the dryer and of its cover, in addition to the instant water content of the product dried. Finally, a linear relation between the thermal capacity of the product dried with a range going from 1100 to 2300 J/kg.K and a defined drying characteristic time will be concluded from this work.